Pubertal hormones predict sex-specific trajectories of pituitary gland volume during the transition from childhood to adolescence - Sarah Whittle; Marjolein Barendse; Elena Pozzi; Nandita Vijayakumar; Julian G. Simmons, PhD (NeuroImage, 2020)
Pituitary gland volume (PGV) increases during childhood and adolescence in a sex-specific manner, and previous research suggests that puberty may be associated with PGV development. However, existing research to date has focused on sex hormones associated with gonadarche. Given the role of the pituitary gland in hypothalamic-pituitary-adrenal (HPA) axis function, the present study investigated associations between PGV development and HPA hormones that play a role in the earlier pubertal phase of adrenarche.Participants were a community sample of 249 children and early adolescents who participated in longitudinal brain imaging and pubertal assessments. Each participant provided data at one or two waves 1.5–3 years apart, resulting in 409 datasets that covered the age range 8–13 years. PGV was estimated from T1-weighted Magnetic Resonance Imaging (MRI) scans, and dehydroepiandrosterone (DHEA), its sulfate (DHEA-S) and testosterone were measured from saliva. Estradiol was measured for a subset of females. Parents reported on physical pubertal development. Linear mixed modeling was used to investigate associations between age, pubertal measures and PGV development.DHEA, DHEA-S and testosterone (in addition to physical maturation) explained variance in PGV development over and above age, and in a sex-dependent fashion. In all cases, associations were stronger, or only present in females. Estradiol was associated with PGV in females, but this did not appear to account for adrenarcheal hormone effects.Our findings suggest a key role for the hormones of adrenarche, the first biochemical phase of puberty, in PGV development. Further research is required to understand the sex-specific role of adrenarcheal and gonadarcheal hormones on the PGV across development.